The Effectiveness of Breastfeeding Education on Improving Knowledge and Breastfeeding Self-Efficacy among Postpartum Mothers in the Practice of Exclusive Breastfeeding - Hidayati, Rizka Dita; Listiana, Akma; Mundari, Risa (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background:Exclusive breastfeeding is an essential strategy to reduce infant morbidity and mortality rates. However, the exclusive breastfeeding coverage in Indonesia has not yet reached the national target. Low maternal knowledge and breastfeeding self-efficacy are factors that influence breastfeeding success. This study aimed to determine the effect of education on knowledge and breastfeeding self-efficacy among postpartum mothers in Karang Maritim Village, Panjang District, Bandar Lampung City.Methods:This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 25 postpartum mothers selected through consecutive sampling. The intervention involved promotive and preventive education on exclusive breastfeeding conducted in four sessions over eight weeks through group-based learning and individual mentoring. Research instruments included a breastfeeding knowledge questionnaire and the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF). The data were analyzed using the paired sample t-test with a significance level of p 0.05.Results:The mean knowledge score increased from 4.65 to 7.58 (Δ = 2.93; p = 0.000), while the mean breastfeeding self-efficacy score increased from 43.80 to 63.88 (Δ = 20.08; p = 0.000). These findings indicate a significant effect of education on improving mothers' knowledge and confidence in breastfeeding.Conclusion:Structured, interactive, and family-based promotive–preventive education effectively enhances knowledge and breastfeeding self-efficacy among postpartum mothers. This intervention can be implemented in community-level breastfeeding education programs as a strategy to increase exclusive breastfeeding coverage.Suggestion: Future research should include additional variables such as workplace support and maternal psychological factors, and use a longitudinal design to examine the sustainability of exclusive breastfeeding practices